Flows in Polymers, Reinforced Polymers and Composites A Multi-Scale Approach - Binetruy, Christophe; Chinesta, Francisco; Keunings, Roland (SpringerBriefs in Applied Sciences and Technology, 2015)
This book gives a detailed and practical introduction to complex flows of polymers and reinforced polymers as well as the flow of simple fluids in complex microstructures. Over the last decades, an increasing number of functional and structural parts, made so far with metals, has been progressively reengineered by replacing metallic materials by polymers, reinforced polymers and composites. The motivation for this substitution may be the weight reduction, the simpler, cheaper or faster forming process, or the ability to exploit additional functionalities. The present Brief surveys modern developments related to the multi-scale modeling and simulation of polymers, reinforced polymers, that involve a flowing microstructure and continuous fiber-reinforced composites, wherein the fluid flows inside a nearly stationary multi-scale microstructure. These developments concern both multi-scale modeling, defining bridges between the micro and macro scales - with special emphasis on the mesoscopic scale at which kinetic theory descriptions apply and advanced simulation techniques able to address efficiently the ever more complex and detailed models defined at different scales. This book is addressed to students (Master and doctoral levels), researchers and professionals interested in computational rheology and material forming processes involving polymers, reinforced polymers and composites. It provides a unique coverage of the state of the art in these multi-disciplinary fields.